2013
DOI: 10.1111/1462-2920.12084
|View full text |Cite
|
Sign up to set email alerts
|

Prokaryotic responses to hydrostatic pressure in the ocean – a review

Abstract: SummaryEffects of hydrostatic pressure on pure cultures of prokaryotes have been studied extensively but impacts at the community level in the ocean are less well defined. Here we consider hydrostatic pressure effects on natural communities containing both unadapted (piezosensitive) prokaryotes originating from surface water and adapted (including piezophilic) prokaryotes from the deep sea. Results from experiments mimicking pressure changes experienced by particle-associated prokaryotes during their descent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
135
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(143 citation statements)
references
References 91 publications
8
135
0
Order By: Relevance
“…All our mesopelagic and bathypelagic samples were decompressed prior to measuring PHP. Whether, decompression of deep sea samples lead to an increased or decreased prokaryotic activity is still a major unknown (Tamburini et al, 2013). In order to estimate the effect of decompression on the E a we subdivided our mesopelagic and bathypelagic data into two depth intervals and found that the apparent E a values were constant between these depth layers (Supplementary Figure S4).…”
Section: Other Factors Affecting the Prokaryote Production To Temperamentioning
confidence: 99%
“…All our mesopelagic and bathypelagic samples were decompressed prior to measuring PHP. Whether, decompression of deep sea samples lead to an increased or decreased prokaryotic activity is still a major unknown (Tamburini et al, 2013). In order to estimate the effect of decompression on the E a we subdivided our mesopelagic and bathypelagic data into two depth intervals and found that the apparent E a values were constant between these depth layers (Supplementary Figure S4).…”
Section: Other Factors Affecting the Prokaryote Production To Temperamentioning
confidence: 99%
“…Water samples were taken in a total of three dives of the remotely operated vehicle (ROV) ABISMO at the same station (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22).25′N, 142-42.75′E) on the Challenger Deep. The temperature and salinity profiles were Significance Although many microbial explorations for hadal sediments began in the 1950s, the hadal water is the least-explored microbial biosphere.…”
Section: Resultsmentioning
confidence: 99%
“…The microbiological and geochemical investigations of hadal waters have been limited (10), in contrast to the long history of hadal benthic microbiological studies occurring since the 1950s (11). To date, many piezophiles and piezotolerant bacteria have been isolated from hadal benthic habitats, and their phenotypical and genomic features have been characterized to be distinct from those of the close relatives obtained from shallow marine environments (12). As one of the major biogeochemical traits, a significantly higher microbial carbon turnover rate has been identified in hadal sediments than that in adjacent abyssal plain sediments (13).…”
mentioning
confidence: 99%
“…Layers bathy (1000-4000 m depth), abyssopelagic (4000-6000 m depth) and hadal environments (N 6000 m depth), form a physically uniform entity characterized by slightly elevated amount of inorganic nitrogen, absence of solar radiation, high hydrostatic pressure (up to 110 MPa), extreme oligotrophy and low temperature (2-3°C), except for the warm Mediterranean, Red, and Sulu Seas (Bartlett, 1992;Tamburini et al, 2013). The food web was supposed to be exclusively dependent on the flux of sinking particulate organic carbon (POC) and semi-labile dissolved organic carbon (DOC) produced by phytoplankton and other epipelagic heterotrophic organisms Hansell et al, 2009).…”
Section: Introductionmentioning
confidence: 99%